Innovating Sales Performance: The Impact of Consumer Behavior, Promotion Strategies, and Service Quality at PT Arta Sedana Ngurah Rai - Astana, I Gusti Made Oka; Meliani, Kadek (Lembaga Riset dan Inovasi Al-Matani, 2024)
The primary objective of this research is to explore the impact of customer behavior, promotions, and service quality on the sales performance of PT Arta Sedana Ngurah Rai. The study's population consists of all customers of PT Arta Sedana Ngurah Rai, with a sample size of 90 individuals. The research employs a quantitative approach, using data obtained through questionnaires and analyzed using multiple regression analysis. IBM SPSS version 25 was utilized as the statistical tool for data analysis. The findings reveal that customer behavior positively and significantly influences sales performance, as indicated by a t-count of 3.804, which exceeds the t-table value of 1.662, with a significance level of 0.000 (< 0.05). Similarly, promotions have a positive and statistically significant relationship with sales performance, with a t-count of 1.778 > 1.662 and a significance level of 0.003 (< 0.05). Furthermore, service quality also positively and significantly impacts sales performance, with a t-count of 4.620 > 1.662 and a significance level of 0.000 (< 0.05).